A Pre-Experimental Study to Assess the Effectiveness of Structured Teaching Programs (STP) on Knowledge Regarding Kwashiorkor and Marasmus Among Mothers of Under Five Year Children in Selected Rural Area of Bilaspur (C.G.) - Tiwari, Jyoti; Abraham, Rachana; Tirkey, Shikha (International Journal of Recent Advances in Multidisciplinary Topics, 2024)
Children are most vital populace for nations, for optimal psychological, physical and emotional growth for its perspective beneficial citizens. Populace below the age group of 5 years comprises 20 percent of total population and are the most high-risk segment for under nutritional disorders. The childhood is the vital phase of the life for laying the basement for optimal wellbeing and sound mind. Citizens of developing countries are the principal victims of under nutrition. Over 800 million children around the worldwide are encountered with under nutrition. More than half of the childhood deaths in growing nations are due the reason of under nutrition. Malnutrition covers a vast continuum of illness including malnutrition of protein calorie and alters the individual’s growth on massive scale across the global. The most dispersed health and under nutrition problem in developing countries including India, is malnutrition of nutrition of calorie and growth retardation. United Nations International Children’s Emergency Funds (UNICEF) document “The Progress for Children” identifies that in the growing world 146 million children underneath 5 years are below weight, predisposing them to serious problems from common childhood ailments. The normal developmental milestone in preschool children includes, naming colors, showing affection and hooping on one foot. The developmental mile stones assessed by how children play, learn, speak, behave and move. Preschool children try to investigate and explore the things surrounding them. Family plays important role in shaping personality of children by this age preschool child should be able to run tricycle, safety use of scissors, understand the sexuality difference, assist themselves to dress and undress, mingle with other children, sing a song and remind the story or part. Problem Statement: A Pre-Experimental Study to Assess the Effectiveness of Structured Teaching Programs (STP) on Knowledge Regarding Kwashiorkor and Marasmus Among Mothers of Under Five Year Children in Selected Rural Area of Bilaspur (C.G.). Objectives of the Study: 1) To assess the pre-test score on knowledge regarding kwashiorkor and marasmus among the mothers of under-five year children in the selected rural area of , Bilaspur (C.G.). 2) To assess the post test level of knowledge regarding kwashiorkor and marasmus under five-year children in selected rural area of Bilaspur (C.G). 3) To evaluate the effectiveness of structured teaching programme in terms of knowledge regarding kwashiorkor and marasmus among the mothers of under-five year children in the selected rural area of, Bilaspur (C.G.). 4) To find out the association between pre test knowledge score regarding kwashiorkor and marasmus mother of under five-year children with their selected sociodemographic variable. Hypothesis: To examine the following hypothesis at 0.05 level of significance: H1: There will be a significant difference between the pre-test and post-test knowledge scores of among mothers of under-five year children. H2: There will be a significant association between knowledge score and selected demographic variables. Research Design: Pre experimental design. (i.e.) one group pre test and post test design was used to accomplish the objective of the study. Setting: The study was conducted in the rural area Pandhi (Anganwadi), Bilaspur. Sample: Sample are Selected by Purposive Sampling Techniques technique was used for the selection of patients. The counts of 60 samples were selected for the study.
Keywords: Structured Teaching Programs; Kwashiorkor; Marasmus